Development and Pilot Evaluation of Sensor-Based Environmental Monitoring and Green Technology Interventions for Pollution Reduction in Indonesian Mining Sites - Muh Arif Idhan; Kasmira Kasmira (Jurnal IPTEK Bagi Masyarakat, 2026)
This study develops and pilot-tests an integrated package of environmentally friendly operational interventions and a sensor-based environmental monitoring system at two mining locations in Indonesia. The research used a pilot multiple-site case study over three months, combining field observation, document review, and repeated measurement of water, air, and soil quality indicators. The analytical focus was on descriptive before–after comparison and compliance-gap assessment, because the pilot dataset was limited to two sites and did not justify inferential statistics. The results show that PM2.5 declined from 58 to 41 µg/m³ at Mine Location A (29.3%) and from 65 to 55 µg/m³ at Mine Location B (15.4%) after intervention. However, several parameters remained above or below the required benchmarks, including turbidity (15–25 NTU versus ≤5 NTU), dissolved oxygen (3.8–4.5 mg/L versus ≥5 mg/L), arsenic (10–12 ppb versus ≤5 ppb), and soil organic matter (2.0–2.5% versus ≥3%). These findings indicate that the monitoring system is effective for early detection and operational feedback, whereas the green technology interventions produced only partial environmental improvement. The study contributes a practical framework for integrating site-level monitoring, threshold-based evaluation, and adaptive environmental management in Indonesia's mining sector. The main implication is that sensor deployment should be scaled together with stronger mine-water treatment, dust suppression, calibration routines, and compliance reporting requirements.